Placental deficiency of the (pro)renin receptor ((P)RR) reduces placental development and functional capacity - Schofield, Lachlan G.; Kahl, Richard G. S.; Rodrigues, Samantha L.; Fisher, Joshua J.; Endacott, Saije K.; Delforce, Sarah J.; Lumbers, Eugenie R.; Martin, Jacinta H.; Pringle, Kirsty G. (Frontiers in Cell and Developmental Biology, 2023)
The (pro)renin receptor ((P)RR; also known as ATP6AP2) is a multifunctional receptor. The (P)RR activates the tissue renin-angiotensin system (RAS) and is also involved in regulating integral intracellular pathways such as V-ATPase and Wnt/-catenin signalling. Given this, the (P)RR may be associated with essential pathways in placentation, however its role within the context of pregnancy remains poorly characterised. The first trimester/extravillous trophoblast cell line, HTR-8/SVneo, underwent an siRNA knockdown where they were incubated for 24 h with a negative control siRNA or siRNA targeting ATP6AP2 mRNA. xCELLigence real-time cell analysis was performed to assess the effect of ATP6AP2 mRNA knockdown on HTR-8/SVneo cell proliferation, migration, and invasion. In subsequent experiments, GFP-encoding lentiviral packaged gene-constructs were used to knockdown (P)RR expression in the trophectoderm of C57/BL6/CBA-F1 mouse blastocysts. Blastocysts were incubated for 6 h with vehicle (no-virus), control virus (non-targeting shRNA and GFP), or (P)RR-knockdown virus ((P)RR shRNA and GFP) before transfer into recipient pseudo-pregnant Swiss CD1 female mice. Fetal and placental tissues were collected and assessed at embryonic age (EA) 10 and 18. (P)RR levels were measured in the labyrinth zone of day 18 placentae and stereological Merz grid analysis was performed to determine the volumetric distribution of trophoblasts, fetal capillaries, and the maternal blood space. We showed that a reduction of ATP6AP2 expression in HTR-8/SVneo cells in vitro, impaired trophoblast proliferation, migration, and invasion. In vivo, decreasing placental labyrinth (P)RR expression adversely effected placental physiology, decreasing placental trophoblast number and total surface area available for exchange, while also increasing maternal blood space. Additionally, decreased (P)RR affected placental efficacy evident by the reduced fetal-placental weight ratio. Our study shows that the (P)RR is necessary for appropriate placental development and function.